2012
DOI: 10.1093/cid/cir1037
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and Motor Deficits in HIV-Infected Ugandan Children With High CD4 Cell Counts

Abstract: Significant motor and cognitive deficits were found in HIV-infected ART-naive Ugandan children with CD4 cell counts of ∼350 cells/μL and percentages of >15%. Study of whether early initiation of ART could prevent or reverse such deficits is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 35 publications
14
134
1
1
Order By: Relevance
“…The BOT-2 has proven adaptable and useful in characterizing the specific aspects of motor impairment associated with HIV in Ugandan children. 18,19 …”
Section: Bot-2mentioning
confidence: 99%
“…The BOT-2 has proven adaptable and useful in characterizing the specific aspects of motor impairment associated with HIV in Ugandan children. 18,19 …”
Section: Bot-2mentioning
confidence: 99%
“…We speculate that suppression of viral replication by ART relieves neurocognitive deficits in both groups of children to near normal levels, effectively eliminating subtype‐specific differences. We had previously observed that high HIV viral load was associated with neurocognitive impairment in Ugandan children who were not on ART 5. In that same cohort, children infected with subtype A who had poorer neurocognitive outcomes also had higher HIV viral load than subtype D‐infected children 8.…”
Section: Discussionmentioning
confidence: 81%
“…The KABC-II maintained its factor structure with Ugandan cerebral malaria survivors 23 and is sensitive to clinical biomarkers of disease status in Ugandan children with HIV. 9,24 The primary outcome variables were the global scores of Sequential Processing (memory), Simultaneous Processing (visual-spatial analysis), Learning (immediate and delayed memory), Planning (executive reasoning), and Knowledge (crystallized intelligence). These (except for Knowledge) are combined into a total mental processing index (MPI).…”
Section: Assessments For Neuropsychological Outcomesmentioning
confidence: 99%
“…28 This test takes about 23 min to administer and is designed to minimize cultural differences, and has been used in Uganda to assess cognitive factors associated with pediatric HIV. 9,24 The TOVA rapidly presents simple geometric stimuli (i. Captain's Log performance measures. The Captain's Log internal evaluator (CLIE) measures of session performance were used to gauge fidelity of training during a training session.…”
Section: Assessments For Neuropsychological Outcomesmentioning
confidence: 99%